QUALITY VILLAGE MANAGEMENT (KB) FOR COMMUNITY WELFARE - Dailin, Dailin; Jauhari, Tontowi; Nasution, Sri Ilham (Universitas Islam Negeri Raden Intan Lampung, 2024)
A large population growth rate has both positive and negative impacts on national economic development. A large population growth rate will positively open up a wide market to foster economic activities that will create community welfare. However, if the large population growth rate is not utilized properly, it will have a domino effect on various problems. The purpose of this research is to provide an overview of the management of Quality Village (KB) in realizing community welfare. This research is literature research where the data used is secondary data obtained from scientific articles and other documents relevant to the research. Data analysis in this study was carried out in three stages, namely data reduction, data categorization, and data verification. The results concluded that the Quality Village (KB) program has contributed to efforts to improve Indonesia's economic development and realize community welfare.